U17XS8, a small nucleolar RNA with a 12 nt complementarity to 18S rRNA and coded by a sequence repeated in the six introns of Xenopus laevis ribosomal protein S8 gene. - Cecconi, F (1994)
U17XS8 RNA is a 220 nt small RNA coded by a sequence repeated in each of the six introns of the gene for ribosomal protein S8 of Xenopus laevis. It is mainly localized in the nucleolus, as shown by in situ hybridization, and it is assembled in a ribonucleoprotein particle (RNP) sedimenting at about 12S, slightly faster than U3 RNP, and with a density of 1.45 g/ml. DNA and RNA microinjections in Xenopus oocytes have shown that U17XS8 RNA is not the product of an independent transcription unit, but is produced by processing of intron sequences of r-protein S8 transcript, as has been recently shown for other small nucleolar RNAs encoded in the introns of other genes. Its accumulation during Xenopus development, oogenesis and embryogenesis, increases in parallel to that of r-protein S8 mRNA. Another interesting feature is the presence in the U17XS8 RNA of a 12 nt sequence complementary to 18S rRNA. The results presented suggest a possible role of this RNA in some step(s) of ribosome assembling in the nucleolus. Some relevant differences between Xenopus U17XS8 RNA and the corresponding human U17 RNA, recently described, have been observed.